Unreliability in Public Transport Chains - F.R. Bruinsma; P. Rietveld; D.J. van Vuuren (Tinbergen Institute, 1999)
In this paper the reliability of travelling by public transport modes is investigated. We deal with the reliability of travel times in public travel chains. Until now the only research in this field has been directed towards the reliability of trips where only one move is made. Therefore, a new element of our approach is that the probability that passengers miss the connection from one part of a chain to the other is taken into account.We use a sample of 300 journeys by public transport chains and operationalise them for three different periods of the week (peak hour, off-peak and during the weekend) according to the official time tables as published by the public transport companies.We use the distribution of arrival and departure times - specified for each public transport mode - to simulate disturbances of the travel times compared to official travel times as published by the public transport companies.
Keywords: 330; Personenverkehr; Eisenbahnpersonenverkehr; Transportzeit; Theorie; Niederlande